2006
DOI: 10.1200/jco.2006.24.18_suppl.1507
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to assess the tolerability and efficacy of RAD-001 (everolimus) with gefitinib in patients with recurrent glioblastoma multiforme (GBM)

Abstract: 1507 Background: The majority of GBMs overexpress EGFR and have PTEN loss leading to activation of AKT signaling. mTOR is a downstream target which is blocked by RAD-001. The addition of an mTOR inhibitor to EGFR blockade by gefitinib may augment downregulation of AKT. Methods: Nineteen patients with GBM were enrolled in a phase I/II protocol open to patients with either hormone refractory prostate cancer or recurrent GBM. Patients on enzyme inducing anti-epileptic drugs (EIAEDs) were excluded, but prior trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…[ 11 ] High grade gliomas are included in ongoing phase II cancer chemotherapy trials at various centers. [ 12 ] In patients with genetic predisposition where there is expression / deletion of certain genes like PTEN, P53 and others, there are phase I and II trials being conducted for such specific subpopulation[ 13 ] In such rare entities, there are not many ongoing phase III trials. Hence, such rare tumors can be referred for ongoing phase I or phase II trials.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] High grade gliomas are included in ongoing phase II cancer chemotherapy trials at various centers. [ 12 ] In patients with genetic predisposition where there is expression / deletion of certain genes like PTEN, P53 and others, there are phase I and II trials being conducted for such specific subpopulation[ 13 ] In such rare entities, there are not many ongoing phase III trials. Hence, such rare tumors can be referred for ongoing phase I or phase II trials.…”
Section: Discussionmentioning
confidence: 99%
“…[67][68][69] Gefitinib was given with everolimus in a phase I/II trial but PFS (2.6 months) was similar to that achieved with monotherapy. 70 Sirolimus was added with erlotinib in a pilot study and with carboplatin in a phase II trial in rGBM patients and showed a PFS-6 of 25 and 14%, respectively. 71,72 The European Organisation for research and treatment of Cancer (EORTC) trial compared the efficacy of erlotinib with TMZ or carmustine in 110 rGBM patients.…”
Section: Molecular-targeted Therapymentioning
confidence: 99%